A Wide-Band Test Fixture for Analyzing Parasitic Effects of RF Passive SMD Components - Xin Cao; Zongxi Tang (International Journal of Antennas and Propagation)
A wide-band test fixture is designed for the measurement of parasitic effects of RF passive SMD (surface mounted devices) components. Two calibration methods, TRM (Thru-Reflect-Match) from 45 MHz to 2 GHz and TRL (Thru-Reflect-Line) from 2 GHz to 12 GHz, are used for error correction. The measurement standards and fixture are designed based on these two calibration methods. For experimental verification, the multilayered ceramic SMD capacitors of Johanson Technology are measured. The parasitic effects of the SMD capacitors are analyzed. The designed fixture is feasible and applicable for quick and accurate measurement of RF passive SMD components.